Formal grammar 15th and 16th international conferences, FG 2010, Copenhagen, Denmark, August 2010, FG 2011, Ljubljana, Slovenia, August 2011, revised selected papers - Nederhof, Mark-Jan; Groote, Philippe (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 15th and 16th International Conference on Formal Grammar 2010 and 2011,collocated with the European Summer School in Logic, Language and Information in July 2010/2011. The 19 revised full papers  were carefully reviewed and selected from a total of 50 submissions. The papers papers deal with the following topics: formal and computational phonology, morphology, syntax, semantics and pragmatics; model-theoretic and proof-theoretic methods in linguistics; logical aspects of linguistic structure; constraint-based and resource-sensitive approaches to grammar; learnability of formal grammar;  integration of stochastic and symbolic models of grammar; foundational, methodological and architectural issues in grammar; mathematical foundations of statistical approaches to linguistic analysis.